The Role of Anchoring Bias in Corporate Financial Forecasting and Budgeting in Indonesia - Judijanto, Loso (Eastasouth Institute, 2025)
Anchoring bias is a significant cognitive bias that affects decision-making processes, particularly in financial forecasting and budgeting. This study investigates the role of anchoring bias in forecasting and financial budgeting among companies in Indonesia using a quantitative approach. A sample of 45 financial professionals from diverse industries participated, with data collected through a structured questionnaire utilizing a 5-point Likert scale. The findings indicate a moderate to high prevalence of anchoring bias, which significantly correlates with forecasting inaccuracies. Regression analysis further reveals that anchoring bias explains 34% of the variance in financial planning errors. These results underscore the critical impact of cognitive biases on financial decision-making, emphasizing the need for targeted strategies to mitigate anchoring bias in corporate settings. Recommendations include training programs, structured decision-making frameworks, and technological support to improve financial accuracy and strategic planning.